LOAD AND RESISTANCE FACTOR DESIGN - S. P. , Narayanan (2013)
Load Resistance Factor Design is more rational method which utilizes advanced probability theory and reliability method compared to the Working Stress Design Method. The WSD and LRFD methods have been reviewed and compared. LRFD design codes have been developed for design of different types of structures using concrete or steel. However, the load and resistance factors to be used in LRFD design are region specific and have to be obtained by calibration. In Malaysia, jacket platforms have been designed using WSD and a need was felt to introduce the rational LRFD method for which ISO 19902 was chosen as the design code. The process of calibration of load and resistance factors for design of jacket platforms was presented and the results obtained discussed.